Chronic Oxidative Stress, Mitochondrial Dysfunction, Nrf2 Activation and Inflammation in the Hippocampus Accompany Heightened Systemic Inflammation and Oxidative Stress in an Animal Model of Gulf War Illness - Shetty, Geetha A.; Hattiangady, Bharathi; Upadhya, Dinesh; Bates, Adrian; Attaluri, Sahithi; Shuai, Bing; Kodali, Maheedhar; Shetty, Ashok K. (Frontiers in Molecular Neuroscience, 2017)
Memory and mood dysfunction are the key symptoms of Gulf war illness (GWI), a lingering multi-symptom ailment afflicting >200,000 veterans who served in the Persian Gulf War-1. Research probing the source of the disease has demonstrated that concomitant exposures to anti-nerve gas agent pyridostigmine bromide (PB), pesticides, and war-related stress are among the chief causes of GWI. Indeed, exposures to GWI-related chemicals (GWIR-Cs) and mild stress in animal models cause memory and mood impairments alongside reduced neurogenesis and chronic low-level inflammation in the hippocampus. In the current study, we examined whether exposure to GWIR-Cs and stress causes chronic changes in the expression of genes related to increased oxidative stress, mitochondrial dysfunction, and inflammation in the hippocampus. We also investigated whether GWI is linked with chronically increased activation of Nrf2 (a master regulator of antioxidant response) in the hippocampus, and inflammation and enhanced oxidative stress at the systemic level. Adult male rats were exposed daily to low doses of PB and pesticides (DEET and permethrin), in combination with 5 min of restraint stress for 4 weeks. Analysis of the hippocampus performed 6 months after the exposure revealed increased expression of many genes related to oxidative stress response and/or antioxidant activity (Hmox1, Sepp1, Srxn1), reactive oxygen species metabolism (Fmo2, Sod2, Ucp2) and oxygen transport (Ift172, Slc38a1). Furthermore, multiple genes relevant to mitochondrial respiration (Atp6a1, Cox6a1, Cox7a2L, Ndufs7, Ndufv1, Lhpp, Slc25a10, Ucp1) and neuroinflammation (Nfkb1, Bcl6, Csf2, IL6, Mapk1, Mapk3, Ngf, N-pac, Prkaca) were upregulated, alongside 73-88% reduction in the expression of anti-inflammatory genes IL4 and IL10, and nuclear translocation and increased expression of Nrf2 protein. These hippocampal changes were associated with elevated levels of pro-inflammatory cytokines and chemokines (Tnfa, IL1b, IL1a, Tgfb, Fgf2) and lipid peroxidation byproduct malondialdehyde in the serum, suggesting the presence of an incessant systemic inflammation and elevated oxidative stress. These results imply that chronic oxidative stress, inflammation, and mitochondrial dysfunction in the hippocampus, and heightened systemic inflammation and oxidative stress likely underlie the persistent memory and mood dysfunction observed in GWI.